2004
DOI: 10.1063/1.1765860
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength control of 1.3–1.6 μm light emission from the quantum dots self-formed in GaAs∕InAs short-period superlattices grown on InP (411)A substrates

Abstract: Articles you may be interested inGaAsSb/GaAsN short-period superlattices as a capping layer for improved InAs quantum dot-based optoelectronics Appl. Phys. Lett. 105, 043105 (2014); 10.1063/1.4891557Wavelength controlled multilayer-stacked linear InAs quantum dot arrays on InGaAsP/InP (100) by selforganized anisotropic strain engineering: A self-ordered quantum dot crystal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A different approach was used by Mori et al [27] to control the dot size and the emission wavelength. Here, GaAs/InAs short period superlattices were grown on (411)A InP.…”
Section: Growth On High-index Substratesmentioning
confidence: 99%
“…A different approach was used by Mori et al [27] to control the dot size and the emission wavelength. Here, GaAs/InAs short period superlattices were grown on (411)A InP.…”
Section: Growth On High-index Substratesmentioning
confidence: 99%
“…5) We have already demonstrated that the 1300-1600 nm wavelength selfformed QDs are fabricated by growing the GaAs/InAs short period SLs on InP(411)A substrates and that the wide and precise photoluminescence (PL) emission wavelength control is possible by regulating the SL period and the InAs monolayer (ML) number. 6) We have already reported their good optical properties and fabricated the light emitting diodes (LEDs) with these QDs as an active layer. 7) However, in the light output versus driving current curves, the output intensity showed saturation for the driving current of over 100 mA.…”
mentioning
confidence: 99%